Acupuncture therapies for cancer-related fatigue: A Bayesian network meta-analysis and systematic review - Tian, Hao; Chen, Yunhui; Sun, Mingsheng; Huang, Liuyang; Xu, Guixing; Yang, Chunyang; Luo, Qin; Zhao, Ling; Wei, Zheng; Liang, Fanrong (Frontiers in Oncology, 2023)
Background: Cancer-related fatigue (CRF) is one of the most commonly reported symptoms impacting cancer survivors. This study evaluated and compared the effectiveness and safety of acupuncture treatments for CRF. Methods: We searched PubMed, Embase, Web of Science, Cochrane Library, China Biology Medicine China National Knowledge Infrastructure, China Science and Technology Journal Database, and WanFang Database from inception to April 2022 to identify eligible randomized controlled trials (RCTs) comparing acupuncture treatments with sham interventions, waitlist (WL), or usual care (UC) for CRF treatment. The outcomes included the Cancer Fatigue Scale (CFS) and Pittsburgh Sleep Quality Index (PSQI), and pair-wise and Bayesian network meta-analyses were performed using STATA v15.0. Results: In total, 34 randomized controlled trials featuring 2439 participants were included. In the network meta-analysis, the primary analysis using CFS illustrated that point application (PA) + UC (standardized mean difference [SMD] = −1.33, 95% CI = −2.02, −0.63) had the highest probability of improving CRF, followed by manual acupuncture (MA) + PA (SMD = −1.21, 95% CI = −2.05, −0.38) and MA + UC (SMD = −0.80, 95% CI = −1.50, −0.09). Moreover, the adverse events of these interventions were acceptable. Conclusion: This study demonstrated that AU or PA + UC have significant effects on CRF. It is evident that acupuncture therapy is not inferior to pharmacologic therapy. Our study provides new insights into potential clinical treatments for CRF. Further studies are warranted to deeply explore the methodological quality of network meta-analysis by incorporating more high-quality RCTs.